Knowledge of Hypertensive Patients Affects Blood Pressure Reduction - Viki Indah Monika; Antonius Rino Vanchapo; Alpian Jayadi; Emanuel Suban Bala Lewar; Juandri Seprianto Tusi; Elladdadi Mark; Kailie Maharjan (Yayasan Adra Karima Hubbi, 2023)
Hypertension is a disease that is often referred to as the Silent Killer, high blood pressure which often does not cause symptoms, is referred to as hypertension when the blood pressure is more than 140/90 mmHg. Knowledge about how to lower blood pressure is very important for people with hypertension. However, several reviews and case reports presenting data on hypertension for lowering blood pressure provide different conclusions. Therefore, the authors are interested in systematically examining the factors that influence blood pressure increases. Articles were searched through the database from 2018 to 2022. Searches were obtained from PUBMED. The keywords used are